Phase relations of Fe3C and Fe7C3 up to 185 GPa and 5200 K: Implication for the stability of iron carbide in the Earth's core. Issue 24 (30th December 2016) - Liu, Jin; Lin, Jung‐Fu; Prakapenka, Vitali B.; Prescher, Clemens; Yoshino, Takashi
Abstract: We have investigated phase relations and melting behavior of Fe3 C and Fe7 C3 using X‐ray diffraction in a laser‐heated diamond cell up to 185 GPa and 5200 K. Our results show that the starting Fe3 C sample decomposes into a mixture of solid orthorhombic Fe7 C3 and hcp‐Fe at above 145 GPa upon laser heating and then transforms into Fe‐C liquid and solid Fe7 C3 at temperatures above 3400 K. Using the intensity of the diffuse scattering as a primary criteria for detecting melting, the experimentally derived liquidus for a bulk composition of Fe3 C fitted with the Simon‐Glatzel equation is T m ( K ) = 1800 × [1 + ( P m − 5.7)/15.10 ± 2.55] 1/2.41 ± 0.17 at 24–185 GPa, which is 500 K higher than the melting curve of iron reported by Anzellini et al. (2013) at Earth's core pressures. The higher melting point and relative stability of Fe7 C3 in Fe‐rich Fe‐C system at Earth's core conditions indicate that Fe7 C3 could solidify out of the early Earth's molten core to become a constituent of the innermost inner core. Key Points: Fe3 C decomposes into a mixture of solid Fe7 C3 and hcp‐Fe above 145 GPa prior to melting Fe3 C liquidus is 5100 K at 185 GPa, which is 500 K higher than Fe melting point by Anzellini et al. Fe7 C3 may solidify out of the early outer core to become a component of the innermost inner core